Financial Development and Financing Constraints : International Evidence from the Structural Investment Model - Love, Inessa (World Bank, Washington, DC, 2014)
The relationship between the financial, and real sides of the economy has long been a topic of intense interest, and debate. The author provides microeconomic evidence that financial development aids growth, by reducing financing constraints that would otherwise restrict efficient firm investment. The author estimates a structural model, based on the Euler equation for investment, using firm-level data from forty countries. The results show a strong negative relationship between the extent of financial market development, and the sensitivity of investment, to the availability of internal funds (a proxy for financing constraints). Considering size effects, business cycles, and the legal environment as plausible alternative explanations, the author finds the results to be robust in all cases.